Fe+3- Mn+4 and Ti+4- Mn+3 interactions effect on the structural, electronic, magnetic and magnetoelectronic properties of perovskite manganites. Issue 3 (1st February 2022) - Singh, Priyanka; Singh, Brajendra; Gupta, Mukul
Abstract: In this study, we report room temperature positive magneto capacitance due to Ti +4 and Mn +3 valence states interactions in La0.7 Pb0.3 Mn0.4 Ti0.6 O3+δ (δ = 0.15) i.e. La0.66 Pb0.3 Mn0.4 Ti0.56 O3 and negative magneto capacitance due to Fe +3 and Mn +4 valance states interactions in Fe doped composition La0.7 Pb0.3 Mn0.4 Fe0.6 O3. Rietveld analysis shows similar structural properties of Fe and Ti doped compositions. Synchrotron X-ray absorption spectroscopy (XAS) studies show (i) the presence of Ti +4, Mn +3 and Mn +4 in La0.66 Pb0.3 Mn0.4 Ti0.56 O3 and (ii) Fe +3, Mn +3 and Mn +4 in La0.7 Pb0.3 Mn0.4 Fe0.6 O3 . At room temperature, Fe doped composition shows nearly three times more magnetic moment in comparison to the magnetic moment of Ti doped composition. La0.7 Pb0.3 Mn0.4 Fe0.6 O3 composition shows maximum ∼64% negative magneto capacitance while La0.66 Pb0.3 Mn0.4 Ti0.56 O3 shows maximum ∼ 12% positive magneto capacitance. Size, quantity, number of d electrons and type of interactions among the valence states Fe +3 (0.645 Å), Ti +4 (0.605 Å), Mn +3 (0.645 Å), Mn +4 (0.53 Å) affect the electronic, magnetic and magnetoelectric properties of La0.66 Pb0.3 Mn0.4 Ti0.56 O3 and La0.7 Pb0.3 Mn0.4 Fe0.6 O3 manganites.